Asymptomatic ocular candida: a case outside the guidance - Roshnee Patel; Lena Wragg; Jas Virdee (Clinical Medicine)
Introduction: Candidaemia carries a high mortality rate among inpatients.1 Deep-seated infection needs to be ruled out to guide both source control and treatment duration.2 Ophthalmic candida can lead to sight-threatening endophthalmitis, although guidelines in both the UK and USA are conflicting as to whether patients with candidaemia but no visual symptoms should be screened for this.3–5 We present a case of a patient who developed candidaemia and was found to have chorioretinitis on routine ophthalmic examination in the absence of any visual symptoms. Materials and Methods: A 76-year-old man was admitted under the medical team with reduced consciousness after a 3-day history of fever, diarrhoea and vomiting. He had type 2 diabetes mellitus with recent surgery on a Charcot foot and a long-term urethral catheter.He was septic on admission with accompanying acute kidney injury. The initial working diagnosis was a catheter-associated urinary tract infection, and the patient started intravenous antibiotics.The patient subsequently grew both group B Streptococcus and Candida albicans in his blood cultures and antimicrobials were accordingly adjusted. Initial investigations into the source of the Candida, such as in the urinary tract, were negative and there was also no evidence of clear deep-seated infection.The microbiology team also suggested an ophthalmology review, despite the patient lacking any visual symptoms or signs.The patient was found to have bilateral chorioretinitis suggestive of ocular candidiasis, requiring a prolonged course of initially intravenous then oral fluconazole. Three weeks after he completed his anti-fungal course, a follow-up ophthalmology review reported that the chorioretinal lesions had resolved and an associated intraretinal haemorrhage was resolving. Results and Discussion: Candida bloodstream infection is increasing in incidence yearly in the UK.6 Candidaemia with evidence of ocular involvement requires at least 1 month of specific anti-fungal agents given the varying tissue penetrance of these drugs.5The Royal College of Ophthalmologists (RCOphth) argue that ophthalmic screening in visually asymptomatic patients is unnecessary because of the low overall prevalence of significant fungal eye disease requiring intervention.4 The Infectious Diseases Society of America suggests that all patients with systemic candidiasis should undergo ophthalmic screening on starting treatment.5 Our case calls into question advice from the RCOphth. The main benefit of early detection and, therefore, treatment of ocular Candida is sight preservation for the affected patient, while also providing evidence of deep-seated infection warranting extended treatment, although the relationship between the severity of chorioretinitis and progression to endophthalmitis is yet to be established.3 Conclusion: Ultimately, a core skill of our job as clinicians is risk assessment: here, assessing the risk and likelihood of severe infection versus the cost of multiple investigations and side-effects of complex drugs. Our patient was investigated outside of RCOphth guidance for candidaemia, and yet he was found to have a deep-seated infection, which ultimately improved with targeted therapy. Guidelines exist to support our decision-making, but we must ensure that we retain our clinical curiosity and tailor our strategy to the patient in front of us.